Implementation of Models for Assessing Professional Competencies Using ICT Tools - KOVALEV, EUGENE; KOVALEVA, NATALIA (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2018)
In the article author examines the methodology for assessing professional competencies in the training of bachelors. The author identifies the role of ICT tools, conducts information modeling and offers software tools for implementing the methodology. In addition, the author gives an example of an expert map for external evaluation of competencies.